KAJIAN REVIEW ARTIKEL : PERAN E-COMMERCE DALAM MENINGKATKAN PENJUALAN - Wahdah, Aliya Fauziah FB; Poppy, Elvina; Lusianto, Kefri; Novita, Ririen; Arum, Vika; Candra, Ridwan (AMMER : JOURNAL OF ACADEMIC & MULTIDICIPLINE RESEARCH; Vol 2 No 03 (2023): EDISI OKTOBER - JANUARIDO - 10.32503/ammer.v2i03.3407, 2023)
The role of e-commerce is very important in today's marketing communication media because it can be used to increase sales. The development of increasingly sophisticated technology makes daily activities easier. By using only mobile phones and computers, one can access things quickly, practically, and easily. Current technological developments certainly have a positive impact, especially for business people. The method used in this study uses the Systematic Literature Review (SLR) method to identify, evaluate, and interpret relevant research results. After going through the search results of 11 previous journals and literature, it can be concluded that the role of e-commerce in sales is very influential, because e-commerce makes it a marketing communication medium and the role of e-commerce as a data carrier for communication strategies in the marketing area is an effective factor. Then, the role of e-commerce as a brand awareness strategy in the marketing area becomes an effective factor. So that the marketing reach is wider, it can be done by creating advertising content according to trends on social media that are frequently visited by consumers. E-commerce also makes social media a target for good communication strategies to consumers and has a strong influence on accessing and encouraging consumers to make purchases.